Stationary environmental studies of the gully steppe of northeastern Ukraine: preliminary results of the 25-year observations - Токарський, В. А.; Ронкін, В. І.; Савченко, Г. О. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
In 1991 a site for long-term monitoring was set in the gully steppe system near the village of Nesterivka. Current site mapping shown that proportion of the area without grazing increased from the initial 10% to 60% due to reduction of the areas with moderate grazing (from 50% to 10%) and intensive grazing (from 40% to 30%). Data and places of the initial arboreal and shrub vegetation encroachment were registered. First phases of the vegetation changes at the last stage of pascual degradation were described. All family sites of the Steppe Marmot settlements were mapped; reducing the marmots’ sites and its dependence on the grazing decrease was registered. Population changes of the most significant mammal species of the gully steppe and adjacent areas are discussed.